Manajemen Program Parenting Bimbingan Baca-Tulis Al Qur'an dengan Metode Yanbu'a bagi Orang Tua di TK Nurul Hikmah Kecamatan Tonjong Kabupaten Brebes (THUFULA, 2017)
Abstract: PARENTING PROGRAM MANAGEMENT OF RECITING-WRITINGAL-QUR'AN WITH YANBU'A METHOD FOR PARENTS IN KINDERGARTENNURUL HIKMAH TONJONG DISTRICT REGENCY OF BREBES. This researchis a field research using qualitative research approach aimed to getdescription about parenting program management process of reciting andwriting al-Qur'an with Yanbu'a method to parents in kindergarten NurulHikmah Tonjong Sub-district of Brebes Regency. The result of this researchshows that parenting program management of reciting and writing Al-Qur’an for parents with Yanbu'a method in Nurul Hikmah kindergarten isdone through four processes. First, develop a parenting program plan, thatis by setting goals and benefits to be achieved and formulate the scheduleof activities and disseminate it to parents and teachers. Second, organizingactivities by assigning tasks and responsibilities of parties related toparenting program activities. Third, carry out parenting programactivities in accordance with the schedule by utilizing various existingresources and create a climate of parenting activities full of familiarityMANAJEMEN PROGRAM PARENTING BIMBINGAN…224between the facilitator and participants. Fourth, controlling parentingprogram activities by monitoring periodically using participantobservation techniques.